Growth, Water Relations, and Photosynthetic Activity Are Associated with Evaluating Salinity Stress Tolerance of Wheat Cultivars - Abeer Hamdy Elhakem (International Journal of Agronomy)
Salinity stress riskiness adversely affects the population by causing food and environmental issues. Moreover, the destructive impacts of salinization differ among various plant cultivars. In the present study, we evaluate the salt stress tolerance among three wheat cultivars based on growth criteria, leaf relative water content (LRWC), and abscisic acid (ABA) level by treating the plants with 0, 40, 80, or 160 mM NaCl. The results revealed that an increase in NaCl concentration caused a massive reduction in growth (shoot and root growth criteria and flag leaf area), photosynthetic pigments (chlorophyll a, chlorophyll b, carotenoids, and total pigments), and LRWC value, but a significant increase in the ABA content in flag leaf in all wheat cultivars. The wheat cultivars were otherwise exposed to anatomical characteristics and photosynthetic gas exchange investigations. NaCl toxicity induced a noticeable reduction in stomatal aperture area (SAA), stomatal conductance (Gs), transpiration rate (Tr), and leaf net photosynthetic rate (Pn). These impacts were remarkable with the 160 mM NaCl treatments for all evaluated parameters. Moreover, Sakha 69 revealed salinity tolerance greater than Giza168, and Sakha8 was the most salt-sensitive cultivar. Consequently, we recognized Sakha 69 as a salt-tolerant cultivar that may be used as parents in breeding programs for new cultivars with enhanced salt tolerance and for further genetic investigations to reveal the genetic strategies controlling the response of salinity stress in the wheat plant.